(3ejcGfjcjI GUGHI GdYehO GdabQjs - (3QTOj eMeO YGOds; (3HQjbY eMeO LGHQ s ((3GdGScfOQjIs (3efTCI GdeYGQas, 1997)
(3GdYehO GdabQj eMhQ h eQcR GdOYe dLejY CLRGA GdLSe dPG jLH GdMaGX Ydjg ef GdGUGHGJ ,h JWQb Gdi GdYfGUQ GdeQJHWI Hg eQhQG HGdLGfH GdJTQjMj dg, h bOe HYV GdGUGHGJ h WQb YdGLgG HGdJeQjfGJ GdHOfjI(B.s
Keywords: (3GdGUGHGJs; (3GdYehO GdabQjs